Pengaruh Penggunaan Media Pembelajaran Interaktif Berbasis Canva Terhadap Hasil Belajar Materi Pancasila dan Potensi Geografis Indonesia Siswa SDN Cipinang 05 Pagi Jakarta Timur - Kusuma, Bukhori brata; Zid, Muhammad; Setiawan, Cahyadi (Prosiding Seminar Nasional Pendidikan, Ilmu-Ilmu Sosial, dan Hukum (SENPISHUM), 2026)
This research aims to find out the effect of learning by using canva-based interactive learning media on student learning outcomes. The subjects in this study are class V students of Cipinang State Elementary School 05 Pagi East Jakarta. The purpose of this research is to find out the influence of the use of canva media on student learning outcomes in pancasila subjects and the geographical potential of Indonesia. This research uses a quasi-experimental method. The data collection techniques used in this study are interviews, observations, questionnaires, tests, and documentation. Data analysis techniques in this study begin with collecting data, compiling data, processing data, presenting data and analyzing numerical data to provide an overview of a phenomenon, event or event. Data analysis helps to describe student learning outcomes which are grouped into five categories: 1). Very high, 2). Height, 3). Medium, 4). Low, 5). Very low. The population of this study is students in class V A and V B with a total of 32 students in class V A (control class) and 31 students in class V B (experimental class). The research results show the tendency that: (1) The increase in student learning results in the experimental class, namely 86,13, is in the high category and achieves completion, which is 90%. (2) Increased learning outcomes before using canva-based interactive learning media in experimental classes (3) Increased student learning outcomes by using canva-based interactive learning media compared to powerpoint media.